Acoustic impact of air operations in the transportation wing No. 11 of the Ecuadorian Air Force - Moreno Ayala, Jessica; Villacis Betancourt, Cristhian; Velasco Castelo, Geoconda (mktDESCUBRE; Vol 1 No 16 (2020): Sixteenth Edition (July - December)DO - 10.36779/mktdescubre.v1i16.529, 2020)
Caring for the environment is a matter of utmost importance, but for them it is necessary to know what is the impact that the different activities generate and thus be able to find a solution or paleative for them. In the present investigation, the measurement of the acoustic impact that the different military air activities of the Transportation Wing No. 11 of the Ecuadorian Air Force, located at the Cotopaxi Airport, generates, as a starting point towards the creation of friendly mitigating alternatives with the environment. To determine the effects, the military hangar was zoned in 16 points and sound pressure levels were measured according to the procedures established in the different national and international regulations, finally obtaining noise level curves; the same ones that allow to clearly visualize to what extent at the auditory level they affect the daily activities of the military part of the airport in the nearby population. Finally, strategic solutions are proposed to be implemented on the personnel working in the military hangar and the population of the areas close to it.